Kinematics of two special endurance trials: A methodological contribution to 400-m performance - Mackala, K.; Omelko, R.; Mroczek, D.; Szczepan, S.; Mastalerz, A. (Journal of Human Kinetics, 2024)
This study aimed to determine changes in the kinematics of sprint steps based on progressive muscular fatigue during high-intensity 350-m and 500-m trials. Twelve elite healthy male 400-m sprinters with a minimum of six years of regular sprint training experience were recruited. They were divided into two groups for the experiment: a 350-m and a 500-m trial group. Time and kinematics of sprinting step motion for specific segments, i.e., starting to final stages of each trial, were obtained using the Opto Jump-Microgate optical measurement system. The starting phase of each sprint was defined as the section without muscular fatigue (noF), and the final phase was the sprint under muscular fatigue (onF). Each last 25 m of the 50-m evaluated section containing ten complete running steps was selected for detailed statistical analysis. Various patterns of temporal and spatial variables of sprinting efforts were observed between 350-m and 500-m trials. Each trial result was influenced by significant individual changes (p < 0.05). All variables indicated that the two distances differed significantly in terms of running kinematics. This was confirmed by significant differences in the mean step frequency (p < 0.001), which presented a difference of 11.75%, and the mean step speed (p < 0.001). As a result of these changes, a hierarchical intermittent endurance training pattern was defined. The research concluded that special endurance (intermittent sprints) based on 350 m differed significantly in kinematics from sprints over 500 m. Therefore, it should be assumed that the distance of 350 m is more similar in its kinematics to the 400-m competition. This should encourage coaches and athletes to apply a 350-m distance in training developing special endurance, especially in the pre-competitive and competitive periods.